Graphene–Bacteriophage Hybrid Nanomaterials for Specific and Rapid Electrochemical Detection of Pathogenic Bacteria - José M. Campiña; António F. Silva; Carlos M. Pereira (Biosensors)
Efficient and rapid detection of bacterial pathogens is crucial for food safety and effective disease control. While conventional methods such as PCR and ELISA are accurate, they are time-consuming, costly, and often require specialized infrastructure. Recently, electrochemical biosensors integrating graphene nanomaterials with bacteriophages—termed graphages—have emerged as promising platforms for pathogen detection, offering fast, specific, and highly responsive detection. This review critically examines all electrochemical biosensors reported to date that utilize graphene–phage hybrids. Key aspects addressed include the types of graphene nanomaterials and bacteriophages used, immobilization strategies, electrochemical transduction mechanisms, and sensor metrics—such as detection limits, linear ranges, and ability to perform in real matrices. Particular attention is given to the role of phage orientation, surface functionalization, and the use of receptor binding proteins. Finally, current limitations and opportunities for future research are outlined, including prospects for genetic engineering and sensor miniaturization. This review serves as a comprehensive reference for researchers developing phage-based biosensors, especially those interested in integrating carbon nanomaterials for improved electroanalytical performance.